2004
DOI: 10.1038/nbt957
|View full text |Cite|
|
Sign up to set email alerts
|

Correction of multi-gene deficiency in vivo using a single 'self-cleaving' 2A peptide–based retroviral vector

Abstract: Attempts to generate reliable and versatile vectors for gene therapy and biomedical research that express multiple genes have met with limited success. Here we used Picornavirus 'self-cleaving' 2A peptides, or 2A-like sequences from other viruses, to generate multicistronic retroviral vectors with efficient translation of four cistrons. Using the T-cell receptor:CD3 complex as a test system, we show that a single 2A peptide-linked retroviral vector can be used to generate all four CD3 proteins (CD3epsilon, gam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
1,074
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,066 publications
(1,098 citation statements)
references
References 28 publications
12
1,074
0
2
Order By: Relevance
“…Encouraged by the successful use of 2A peptides in g-retroviral vectors to express multiple genes in one construct, 24,25,27 we attempted to develop lentiviral vectors expressing antitumor antigen-specific TCRs using different 2A peptides. In Figure 1a, the amino acids from different 2A peptides are illustrated and the conservative domains highlighted.…”
Section: A Peptides Along With Furin and Spacer Facilitate Transgenementioning
confidence: 99%
See 3 more Smart Citations
“…Encouraged by the successful use of 2A peptides in g-retroviral vectors to express multiple genes in one construct, 24,25,27 we attempted to develop lentiviral vectors expressing antitumor antigen-specific TCRs using different 2A peptides. In Figure 1a, the amino acids from different 2A peptides are illustrated and the conservative domains highlighted.…”
Section: A Peptides Along With Furin and Spacer Facilitate Transgenementioning
confidence: 99%
“…It has been reported that in g-retroviral constructs, expression of multiple genes linked with 2A peptides can be facilitated by a spacer sequence (GSG) ahead of the 2A peptides. 25,27 We designed several constructs combining a spacer (SGSG or GSG) and furin (R-A-K-R) 28 cleavage site with different 2A peptides in bicistronic lentiviral vectors (Figure 1b).…”
Section: A Peptides Along With Furin and Spacer Facilitate Transgenementioning
confidence: 99%
See 2 more Smart Citations
“…To achieve simultaneous expression of reprogramming factors, cDNA encoding as many as five reprogramming factors connected by the 2A peptide sequence from the foot-and-mouth disease virus was cloned in a single vector. Individual proteins were produced through a "ribosomal skipping" mechanism mediated by the 2A peptide (Szymczak et al, 2004;Yusa et al, 2009). In the case of the piggyBac system, after successful generation of iPS cells, the reprogramming cassette can be removed by piggyBac transposase without footprint and transgene-free iPS cells were obtained (Yusa et al, 2009).…”
Section: Viral-free Approaches That Do Not Cause Genetic Alterationmentioning
confidence: 99%